A review of the baconii species group of the termitophilous genus Orthogonius Macleay (Coleoptera: Carabidae: Orthogoniini) - Tian, Mingyi; Deuve, Thierry (Zootaxa, 2016)
The baconii species group of the termitophilous carabid genus Orthogonius Macleay, 1825, is defined and reviewed. This group is known only from southern Asia and so far recorded by two species: Orthogonius baconii Chaudoir, 1871, from India and O. nepalensis Habu, 1979, from Nepal. Two new species are described and illustrated: O. rogueti n. sp. from southern India and O. ceylanicus n. sp. from Sri Lanka. In addition, a key to all species of this species group is provided.